Gracillin shows potent efficacy against colorectal cancer through inhibiting the STAT3 pathway. Issue 2 (1st December 2020) - Yang, Lehe; Zhu, Tianru; Ye, Hua; Shen, Yili; Li, Zhiping; Chen, Luye; Wang, Canwei; Chen, Xia; Zhao, Haiyang; Xiang, Youqun; Xiao, Zhongxiang; Zhao, Chengguang; et al.
Abstract: Colorectal cancer (CRC) accounts for about 10% of all annually diagnosed cancers and cancer‐related deaths worldwide. STAT3 plays a vital role in the occurrence and development of tumours. Gracillin has shown a significant antitumour activity in tumours, but its mechanism remains unknown. The human CRC cell lines HCT116, RKO, and SW480 and immunodeficient mice were used as models to study the effects of gracillin on cell proliferation, migration and apoptosis. These were evaluated by cell viability, colony formation, wound‐healing migration and cell apoptosis assays. Luciferase reporter assay, and immunostaining and western blot analyses were used to explore the specific mechanism through which gracillin exerts its effects. Gracillin significantly reduces viability and migration and stimulates apoptosis in human CRC cells. It also significantly inhibits tumour growth with no apparent physiological toxicity in animal model experiments. Moreover, gracillin is found to inhibit STAT3 phosphorylation and STAT3 target gene products. In addition, gracillin inhibits IL6‐induced nuclear translocation of P‐STAT3. Gracillin shows potent efficacy against CRC by inhibiting the STAT3 pathway. It should be further explored as a unique STAT3 inhibitor for the treatment of CRC.